ANALISIS EFEKTIVITAS SISTEM INFORMASI MANAJEMEN ASN DALAMPEMUTAKHIRAN DATA KEPEGAWAIAN DI BPKAD GARUT - Neng Nida Nurfadilah; Tedi Budiman (Information System Journal, 2026)
Personnel data must be updated quickly, accurately, and in an integrated manner to support civil service governance. To meet these needs, the local government has implemented the ASN Management Information System (SIMASN). The purpose of this study was to evaluate SIMASN's effectiveness in updating personnel data at the Garut Regional Revenue and Expenditure Agency (BPKAD) and to identify factors that support and hinder its utilization. Analysis of the accuracy, speed, and ease of data updating at BPKAD Garut was conducted using an interactive model analysis. Data was collected through observation, interviews, and documentation with SIMASN users. The results showed that SIMASN effectively updated employee data. The system's suitability for administrative needs and ease of access were key supporting factors. Challenges that arose were related to limited infrastructure and user digital literacy. These inhibiting factors included a lack of employee awareness in updating data independently, limited digital literacy skills, and suboptimal integration with the BKN central databas.